A study on nucleation kinetics of Carbamazepine-Fumaric Acid form a cocrystal - Said, Zuliyana (2017)
Nucleation kinetics study has a great value for better plan and process of industrial crystallizer. However, the analysis of nucleation kinetics for Carbamazepine (CBZ)- Fumaric Acid (FUM) has not yet been studied. The nucleation kinetics of a solution system can be estimated from the measured metastable zone width (MSZW). Thus, the objective of this paper is to study the nucleation kinetics of CBZ-FUM form A cocrystal by utilizing polythermal crystallization in a batch reactor equipped with refrigerated bath. First, the CBZFUM Form A cocrystals were prepared by utilizing a stoichiometric ratio of 1:1. The nucleation kinetics of CBZ- FUM, were estimated by using Nývlt’s approach. By employing the polythermal technique, the crystallization temperature at the dissolution temperature for every cooling rate and concentration were recorded and the analysis shows that the MSZW had increased as the cooling rate and the concentration increased. The estimated MSZW were plotted as a log function of MSZW versus cooling rate which were used to estimate the nucleation parameters. This study found that the nucleation rate increase as the cooling rate and the solute concentration increase. In addition the characterization of the cocrystal using FTIR and optical microscope shows that there are new bonds formed in the cocrystals, however, by comparing the results with CBZ-FUM form B cocrystals, it is found that some concentration form CBZ-FUM form A cocrystal instead of CBZ-FUM form A cocrystal and all cocrystal has plate-like morphology and the shape of cocrystal elongated as the cooling rate decrease